2021
DOI: 10.1002/ptr.7057
|View full text |Cite
|
Sign up to set email alerts
|

Icariin reduces Glu‐induced excitatory neurotoxicity via antioxidative and antiapoptotic pathways in SH‐SY5Y cells

Abstract: Excessive glutamate (Glu) can lead to significant effects on neural cells through the generation of neurotoxic or excitotoxic cascades. Icariin (ICA) is a main active ingredient of Chinese Medicine Berberidaceae epimedium L., and has many biological activities, such as antiinflammation, antioxidative stress, and anti‐depression. This study aims to evaluate the effect of ICA on Glu‐induced excitatory neurotoxicity of SH‐SY5Y cells. The cell viability assay was evaluated by the CCK‐8 assay. The apoptosis, reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…EAAs participated in synaptic excitatory transmission and promoted learning and memory in physiological status. However, prolonged exposure to excessive EAAs can overly activate their receptors and evoke significant effects on neural cells through the generation of neurotoxic or excitotoxic cascades [ 33 , 34 ] and increase sensitivity to excitotoxic injury. Therefore, the significant increase of glutamic acid and aspartic acid after stimulation might be one of the pathogenesis of aconitine neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EAAs participated in synaptic excitatory transmission and promoted learning and memory in physiological status. However, prolonged exposure to excessive EAAs can overly activate their receptors and evoke significant effects on neural cells through the generation of neurotoxic or excitotoxic cascades [ 33 , 34 ] and increase sensitivity to excitotoxic injury. Therefore, the significant increase of glutamic acid and aspartic acid after stimulation might be one of the pathogenesis of aconitine neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, efflux of glutamic acid and decreased intracellular glutamic acid could reduce GSH synthesis as well. GSH depletion leads to the accumulation of ROS and the consumption of SOD enzyme [ 12 , 27 , 33 , 39 ]. Our experimental results suggested that the intracellular Ca 2+ level of HT22 cells was significantly increased and the activity of Ca 2+ -ATPase was significantly inhibited after aconitine stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…ICA has been revealed by many studies to play a crucial role in antioxidation ( Liu XJ. et al, 2021 ; Zheng et al, 2021 ) and anti-inflammatory ( Guangtao et al, 2021 ; Zhang et al, 2022 ). Hua et al found that IL-1β induces significant expression of COX-2 and iNOS and stimulates the production of PGE2 and nitric oxide in human NP cells ( Hua et al, 2018 ).…”
Section: Phytochemicals For the Treatment Of Idd By Targeting Inflamm...mentioning
confidence: 99%
“…In addition, ICA by inhibiting NF-κB signal activation and NLRP3-inflammasome/caspase-1/IL-1β axis plays an antidepressant-like role in CUMS model of depression in rats [26]. Otherwise, ICA reduces Glu-induced excitatory neurotoxicity through antioxidant and anti-apoptotic pathways in SH-SY5Y cells [27]. However, whether ICA is beneficial for the depression via ameliorating neuronal apoptosis in the hippocampus is still unknown.…”
Section: Introductionmentioning
confidence: 99%